Pengaruh Efektivitas Penggunaan Sistem Pembayaran E-Tilang Terhadap Perilaku Keuangan Masyarakat Di Polres Banyuasin Provinsi Sumatera Selatan: (Studi Kasus Pada Masyarakat Pangkalan Balai Tahun 2023) - Fitri Lisdayanti; Moh.Ihsan; Firmansyah Firmansyah (Universitas 45 Surabaya, 2024)
Technological developments in the financial system have of course brought changes to aspects of human life, especially in payment methods which are now changing and are commonly known as digital payments or E-Tilang. This research is a quantitative study which aims to determine the effect of the effectiveness of using the E-Ticket system on people's financial behavior, where the sample in this study is 100 people in the Pangkalan Balai area, Banyuasin Regency according to data on total cases based on vehicles affected by E-Tickets. and members of the Banyuasin Police Traffic Unit. The data used is primary data and secondary data. Determination of the sample using non-probability sampling. The analysis tool used is SmartPLS (Partial Least Square) 4.0 by testing the outer model and inner model.